TG-FTIR and Py-GC/MS study on pyrolysis mechanism and products distribution of waste bicycle tire. (1st November 2018) - Xu, Fanfan; Wang, Bo; Yang, Dan; Ming, Xue; Jiang, Yuan; Hao, Junhui; Qiao, Yingyun; Tian, Yuanyu
Highlights: Two main pyrolysis stage of waste bicycle tire can be observed from TG. The release characteristics of volatiles was consistent with pyrolysis behavior. FTIR spectrum at different temperature indicated two main pyrolysis stages. Pyrolysis mechanism of waste bicycle tire was free radical mechanism. Abstract: Pyrolysis of waste tire is attracting widespread interest recently because of the great potential in waste valorization treatment. In this study, the thermal decomposition behavior, pyrolysis mechanism and products distribution of waste bicycle tire were investigated by means of TG-FTIR and Py-GC/MS. According to the TG results, two main pyrolysis stages of waste bicycle tire were observed, which were considered as the decomposition of rubber (285–531 °C) and further pyrolysis of pyrolytic products (663–847 °C), respectively. The volatiles release characteristics and FTIR spectrum at different temperatures exhibited good consistency with pyrolysis behavior. A detail information of pyrolysis products was analyzed by Py-GC/MS, which mainly include gaseous, alkenes and aromatics. The pyrolysis mechanism of waste bicycle tire was belong to free radical reaction, and the possible further pyrolysis pathway of D-limonene and styrene was also presented. Moreover, the products distribution under different pyrolysis final temperatures and heating rates conditions were summarized. Thus, this study could enhance our understanding on more specific details for the pyrolysis process of waste tire to some extent.